Choosing the type of equivalent circuit of traction substation when calculating short-circuit currents in 25 kV power supply system - E. P. Figurnov; Yu. I. Zharkov; N. A. Popova (Вестник Научно-исследовательского института железнодорожного транспорта)
When calculating short circuit currents in the traction network, it is necessary to take into account the input resistance of the traction substation, including the resistance of the transformers of the substation and the resistance of the power supply system. The input resistance during short circuit is determined based on the equivalent circuit of the external power supply system, of which this traction substation is an integral part. Traditionally equivalent circuit of a three-phase system has the form of a star, in which the resulting resistances in each phase are connected in series with a source of phase electromotive force, and these sources have a common point. Another equivalent circuit in the form of a triangle is possible, in which on each side the resulting resistances are connected in series with the source of linear electromotive force. It is important to note that neither one nor the other type of equivalent circuit is determined by the connection scheme of the transformer windings of the traction substation. It is only necessary to take into account the absence of a circuit for zero sequence currents. All elements of the equivalent circuit, as is known, should be brought to uniform basic conditions. If the parameters of these elements are expressed in named units, then the basic values are the effective voltage values of the main stage and the rated power of the power transformer of the traction substation. If the components of one and the other equivalent circuits are reduced to one stage of the operating voltage, for example 27.5 kV, then for the same elements of the power supply system, the resistance values in the equivalent circuit in the form of a triangle are three times larger than in the equivalent circuit in the form of a star. In this case, the input resistances of the traction substation for the one and the other equivalent circuits are absolutely identical. Therefore, in the calculation of short circuit currents of the traction network, you can use any of these equivalent circuits of the power supply system and traction substation. Formulas for calculating the resistances of the elements of the power supply system and electrical installations, given in the standards, manuals and reference books, relate to the equivalent circuit of the short circuit in the form of a star. When using an equivalent circuit in the form of a triangle, these resistances must first be tripled, and then divided by three when calculating the short-circuit currents. The meaninglessness of such an operation is obvious. The equivalent circuit of the traction substation and the external power supply system in the form of a triangle when calculating short circuits in the traction network has no advantages compared to the traditional equivalent circuit in the form of a star. The information on the linear currents on the primary and secondary windings of the traction substation transformer during a short circuit in the traction network is given, which is necessary to select the settings of its relay protection kit.